Variably improved microbial source tracking with digital droplet PCR - Nshimyimana, Jean Pierre (2019)
This study addressed whether digital droplet PCR (ddPCR) could improve sensitivity and specificity of human-associated Bacteroidales genetic markers, BacHum and B. theta, and their quantification in environmental and fecal composite samples. Human markers were quantified by qPCR and ddPCR platforms obtained from the same manufacturer. A total of 180 samples were evaluated by each platform including human and animal feces, sewage, and environmental water. The sensitivity of ddPCR and qPCR marker assays in sewage and human stool was 0.85–1.00 with marginal reduction in human stool by ddPCR relative to qPCR (<10%). The prevalence and distribution of markers across complex sample types was similar (74–100% agreement) by both platforms with qPCR showing higher sensitivity for markers in environmental and composite samples and ddPCR showing greater reproducibility for marker detection in fecal composites. Determination of BacHum prevalence in fecal samples by ddPCR increased specificity relative to qPCR (from 0.58 to 0.88) and accuracy (from 0.77 to 0.94), while the B. theta assay performed similarly on both platforms (specificity = 0.98). In silico analysis indicated higher specificity of ddPCR for BacHum was not solely attributed to reduced sensitivity relative to qPCR. Marker concentrations measured by ddPCR for all sample types were consistently lower than those measured by qPCR, by a factor of 2.6 ± 2.8 for B. theta and 18.7 ± 10.0 for BacHum. We suggest that differences in assay performance on ddPCR and qPCR platforms may be linked to the characteristics of the assay targets (that is, genes with multiple versus single copies and encoding proteins versus ribosomal RNA) however further work is needed to validate these ideas. We conclude that ddPCR is a suitable tool for microbial source tracking, however, other factors such as cost-effectiveness and assay-specific performance should be considered.